2003
DOI: 10.1161/01.str.0000086753.00555.0d
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Homocysteine Was Associated With Hemorrhagic and Ischemic Stroke, but Methylenetetrahydrofolate Reductase Gene C677T Polymorphism Was a Risk Factor for Thrombotic Stroke

Abstract: Background and Purpose-It is still controversial whether elevated plasma homocysteine and the C677T polymorphism of methylenetetrahydrofolate reductase (MTHFR) gene are risk factors for stroke. The aim of the present study was to investigate the association between the 2 factors and stroke in Chinese in a large case-control study. Methods-We recruited 1823 stroke patients (807 cerebral thrombosis, 513 lacunar infarction, 503 intracerebral hemorrhage) and 1832 controls. Total plasma homocysteine was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
141
2
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 45 publications
12
141
2
5
Order By: Relevance
“…Methylenetetrahydrofolate reductase (MTHFR), apolipoprotein E (ApoE), and angiotensin-converting enzyme (ACE) were chosen for further analysis, as, on review, those three genes were found to be studied well in Asian populations. Ten studies of MTHFR (Morita et al 1998;Zhang and Dai 2001;Wu et al 2001;Li et al , 2003Choi et al 2003;Baum et al 2004;Alluri et al 2005;Fang et al 2005;Gao et al 2006), six studies for ApoE (Kokubo et al 2000;Luthra et al 2002;Um et al 2003a;Jin et al 2004;Lin et al 2004;Gao et al 2006), and six studies of ACE (Doi et al 1997;Nakata et al 1997;Um et al 2001Um et al , 2003aGao et al 2006) gene polymorphisms were found to meet our selection criteria and were therefore included in the meta-analysis (Tables 2, 3 and 4). Because of unavailability of genotype data, two studies of ApoE polymorphism (Nakata et al 1997;Chowdhury et al 2001) were excluded for the present analyses.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…Methylenetetrahydrofolate reductase (MTHFR), apolipoprotein E (ApoE), and angiotensin-converting enzyme (ACE) were chosen for further analysis, as, on review, those three genes were found to be studied well in Asian populations. Ten studies of MTHFR (Morita et al 1998;Zhang and Dai 2001;Wu et al 2001;Li et al , 2003Choi et al 2003;Baum et al 2004;Alluri et al 2005;Fang et al 2005;Gao et al 2006), six studies for ApoE (Kokubo et al 2000;Luthra et al 2002;Um et al 2003a;Jin et al 2004;Lin et al 2004;Gao et al 2006), and six studies of ACE (Doi et al 1997;Nakata et al 1997;Um et al 2001Um et al , 2003aGao et al 2006) gene polymorphisms were found to meet our selection criteria and were therefore included in the meta-analysis (Tables 2, 3 and 4). Because of unavailability of genotype data, two studies of ApoE polymorphism (Nakata et al 1997;Chowdhury et al 2001) were excluded for the present analyses.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…The majority of the unbound portion of Hcys is oxidized to form dimers (homocystine) or combined with cysteine to form mixed disulphides (Mansoor et al 1992;Ramakrishnan et al 2006). The excess of Hcys concentration is described in many human pathologies, including neurodegenerative diseases (Ravaglia et al 2005), thrombosis (Harpel et al 1996) and thrombosis-related diseases, like stroke (Boysen et al 2003;Li et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Folate deficiency increases total homocysteine (tHcy) levels (4). Hyperhomocysteinemia is one of the risk factors of cardiovascular disease (4,5) and neural tube defects (NTDs) (6). Maintaining adequate blood folate levels and controlling tHcy levels are important in preventing these diseases.…”
mentioning
confidence: 99%